The democratization of intangible luxury. Issue 6 (2nd September 2019) - Ramadan, Zahy
Abstract : Purpose: The notion of luxury has changed due to the democratization and the fast adoption pace of intangible luxury service providers embedding voice-controlled assistants. In particular, Amazon's Echo Look is expected to further democratize luxury services and consumer experience; indeed, this camera-based device acts as a personal consultant as it provides fashion advices based on the pictures of its users. Nonetheless, as the Echo Look proliferates the market, concerns around its potential disruption to the marketplace alongside usage-related issues, such as privacy, will arise. The paper aims to discuss these issues. Design/methodology/approach: The research adopted an exploratory approach using elite interviewing. The sample included 17 experts in the fields of digital marketing, fashion consulting, information technology security and retailing. Findings: The study pioneers the discussion on how interactive voice-activated assistant (IVA) devices can potentially outweigh concerns around safety and privacy through providing luxury-like personalized services. To that end, the Echo Look device was taken as the key example based on the unique features and benefits it provides to its users, namely, in being perceived as a personal fashion consultant. Originality/value: The literature on intangible luxury based on IVA devices is still nascent. This study fills a considerable gap in the literature related to retailers' technological innovations aimed at democratizing luxury-like personalized experiences.